Socio-Economic Impacts of COVID-19 on Working Mothers in France - Lambert, Anne; Girard, Violaine; Guéraut, Elie (Frontiers in Sociology, 2021)
Beyond its devastating consequences for public health, the COVID-19 pandemic had a major impact on gender inequalities, labour markets and families. Compared to many European countries, the French approach to lockdown was among the more stringent, although the measures taken by the French government to support employment, to some extent, mitigated the worst effects of the crisis on families. This article analyses the implications of COVID lockdown restrictions on gender equality and well-being for couples with children in France. The study adopted a multidimensional approach to gender inequalities associated with paid work and various dimensions of living conditions, involving gender-differentiated access to personal work spaces in the home, personal leisure time outside the home, and local support networks during the first phase of lockdown (March−June 2020). Drawing on data from the COCONEL survey, carried out by the Institut national d’études démographiques on a quota sample of the French adult population in April/May 2020, the authors controlled for variables including socio-economic status, age, family structure and place of residence. The survey data was complemented by a longitudinal set of in-depth interviews enabling the research team to capture the differential effects of the pandemic within couples. The main findings indicate that, despite the frequency of dual-employment arrangements for heterosexual couple households with dependent children, French mothers were nevertheless more likely to reduce their working time and/or withdraw from the labour market. Within the households surveyed, mothers were less likely than fathers to leave the home during the day, particularly for personal leisure activities. The presence of children in households increased gender inequality in both employment and living conditions across all socio-economic categories. In conclusion, the authors consider whether the pandemic might have a long-term impact on gender norms and inequalities within families, and how the findings about changes in gender inequalities could be used to inform public policy development.